Development of International Economic Integration (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The development of international economic integration (IEI) is analyzed taking into account the unification of the markets of countries for several centuries on different continents (Europe, North America, Africa). Although the issue of integration is debatable, at the same time more than ten customs unions were able to revive after the Second World War. Positive consequences of the first separate trade and economic associations and their influence on the further development of integration processes are revealed. The deepening of IEI have been confirmed, the analysis of waves of integration of the twentieth century (taking into account the time periods) shows the growth of the number of groupings, in particularly between countries of different levels of economic development, the expansion of the range of issues that are covered by agreements, the growth of bilateral agreements, in particular between countries in different regions, etc. It is noted a crossing of free trade agreements (this is typical especially for Asian countries), the emergence of schemes «hub-and-spoke», its influence on large and smaller countries. The features of preferential rules and the expediency of their application depending on the circumstances are considered. The significant influence of IEI and the need to take into account the intensification of integration of large developing countries (China, Brazil, India, etc.) are justified, in particular, their entry to the markets of other developing countries.
Keywords: international economic integration, development, trends, regional trade agreement, integration grouping